The study of Rydberg gas chemistry by fast flow glow discharge mass spectrometry. - Paul Michael Dickinson (2008)
This study concerns the analysis of processes occurring within, and fundamental characteristics of the flowing afterglow of a fast flowing direct current glow discharge plasma by both mass spectrometric and electrical diagnostic techniques. The evidence presented within this thesis indicates that the glow discharge plasma studied contains a high density of very highly excited state, Rydberg species. Classically, glow discharge plasma is considered to be a partially ionised gas, the chemistry of which is dominated by processes involving charged particles (ions and electrons). However, under the conditions of the fast flow glow discharge source it is thought that the formation and stabilisation of Rydberg atoms is highly favourable, and thus the plasma chemistry can be described by a Rydberg gas model. Theoretical thermodynamic and kinetic data based on calculations (unpublished at the time of submission) performed by Dr R. S. Mason which corroborate this model are also presented. Studies of the influence of the magnitude and polarity of applied the ion exit bias on the electrical properties of the flowing afterglow plasma and active discharge region were undertaken, often in situ with mass spectrometric measurements. Comparison of the electrical and mass spectrometric measurements has provided valuable information about the properties of the Rydberg gas plasma and the ionisation processes within the afterglow plasma. The results of the electrical studies (current and double probe measurements) could not be explained for an ion electron medium. The reactions of secondary gases (H[2], CO, CO[2], N[2], CF[4] and CH[4]) and organic vapours to the flowing afterglow plasma have been studied for a range of conditions. The results of which cannot all be explained by ion-molecule processes, and seemingly conform to the Rydberg gas model.